Benzyl substituted imidazolium ionic liquids as efficient solvent-free catalysts for the cycloaddition of CO2 with epoxides: Experimental and Theoretic study. (December 2017) - Wang, Tengfei; Zheng, Danning; Ma, Yuan; Guo, Jiayi; He, Zhipeng; Ma, Bin; Liu, Lianhuan; Ren, Tiegang; Wang, Li; Zhang, Jinglai
Highlights: Eight benzyl substituted imidazolium ionic liquids are firstly synthesized. They are efficient homogeneous catalysts for cycloaddition of CO2 with PO. The reaction condition is benign with high product yield. No solvent and co-catalyst are required. The reaction mechanism is elucidated by DFT calculation. Abstract: A series of low-cost and easily prepared benzyl substituted imidazolium ionic liquids are firstly synthesized and employed as catalyst for the cycloaddition of carbon dioxide with epoxides without any solvent and co-catalyst. The synthesized imidazolium ionic liquids are characterized by 1 H NMR, HRMS, and MS. The influence of different substituted groups in cation and reaction parameters on catalytic activity is investigated. The highest conversion yield of cyclic carbonate (94.89%) could be achieved with slight amount of catalyst (0.25 mol%) under 130 °C and 2.0 MPa during 4 h. Meanwhile, the mechanisms of cycloaddition of carbon dioxide with epoxides catalyzed by four benzyl substituted ionic liquids with different substituted groups are investigated by theoretical calculations. The role of hydrogen bond and other noncovalent interactions played in catalytic process is further uncovered to deeply understand the difference of various catalysts from atomistic level.